2021
DOI: 10.1075/pbns.326.11haa
|View full text |Cite
|
Sign up to set email alerts
|

Extending sequences of other-initiated repair in Finnish conversation

Abstract: This paper explores other-initiated repair, or more specifically, extended repair sequences. In extended cases, the repair turn does not immediately resolve the trouble, and the speaker needs to produce a new repair initiation.Drawing on a collection of 458 other-initiations of repair in naturally occurring everyday interaction in Finnish, we show how the distribution of the outcomes of different types of initiations clearly differs. Typically, candidate understandings and open class repair initiations do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…To date, no thorough research has been conducted on the prosody of open-class repair initiators in Finnish. However, Routarinne (2003) and Haakana (2008; have observed that expressions whose sequential position resembles that of open-class initiators are used with different kinds of prosodies and may become interpreted for example as news receipts or expressions of astonishment rather than answer-seeking questions.…”
Section: Research On Affectmentioning
confidence: 99%
“…To date, no thorough research has been conducted on the prosody of open-class repair initiators in Finnish. However, Routarinne (2003) and Haakana (2008; have observed that expressions whose sequential position resembles that of open-class initiators are used with different kinds of prosodies and may become interpreted for example as news receipts or expressions of astonishment rather than answer-seeking questions.…”
Section: Research On Affectmentioning
confidence: 99%